Advancing battery thermal management: Future directions and challenges in nano-enhanced phase change materials-based systems - Mahendran, Samykano (Elsevier, 2025)
The widespread adoption of lithium-ion (Li-ion) batteries in electric and hybrid vehicles has garnered significant attention due to their high energy density, impressive power-to-mass ratio, and extended lifespan. However, challenges like non-uniform temperature distribution, suboptimal energy storage, and slower release rates have surfaced. The rising incidents of battery explosions underscore the urgent need for a thorough understanding of Li-ion battery technology, particularly in thermal management. This knowledge is vital for maintaining batteries within an optimal temperature range, improving operational efficiency, and ensuring stability and safety. This review section meticulously explores critical aspects of battery thermal management, focusing on the process of heat generation and transfer within the cell and module. It also examines the thermal management challenges through active and passive techniques, emphasizing advancements in heat transfer methodologies. The investigation of integrating nano-enhanced phase change materials (NePCMs) with Li-ion batteries is particularly noteworthy as a promising approach to enhance thermal conductivity and management. The review comprehensively elaborates on the functions, strategies, emerging concerns, integration methodologies, and benefits of NePCMs, thoroughly examining their impact on thermal management. This comprehensive review anticipates advancements in this vital domain, envisioning development trends and prospects associated with the application of NePCMs in battery thermal management.